PENENTUAN DERAJAT ASILASI (DA) DENGAN METODE BASE LINE DARI SINTESIS N-ALDIMIN KITOSAN - Soma, Yolanda V. A; Daniel, Daniel; Saleh, Chairul (JURNAL ATOMIK, 2018)
Determination Degree of Acylation (DA) with the baseline method from the synthesis of N-Aldimin Chitosan was obtained from the acylation reaction between chitosan and acetaldehyde. The formation of N-Aldimin Chitosan is supported by the data of FT-IR spectroscopy in the wave number 3441.01 cm-1 shows the stretching vibration of OH of chitosan and absorption peaks in the area of wave number 1627.92 cm-1 and 1566.20 cm-1 is vibration C=N which identifies the formation aldimine chitosan. Wavenumber 2924.09 cm-1 shows the C-H stretching vibration as evidenced by a wave number 1404.16 cm-1 which is C-H bending and C-O absorption at wavenumber 1087.85 cm-1. Acylation degree (DA) obtained by 81.33%.